2008
DOI: 10.1590/s0100-879x2008005000004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective analysis of different algorithms for the diagnosis of hepatitis C virus infection

Abstract: We compared the cost-benefit of two algorithms, recently proposed by the Centers for Disease Control and Prevention, USA, with the conventional one, the most appropriate for the diagnosis of hepatitis C virus (HCV) infection in the Brazilian population. Serum samples were obtained from 517 ELISA-positive or -inconclusive blood donors who had returned to Fundação Pró-Sangue/Hemocentro de São Paulo to confirm previous results. Algorithm A was based on signal-to-cut-off (s/co) ratio of ELISA anti-HCV samples that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In addition, through the use of a lesser number of test kits, blood banks could gain further cost reductions by using a lesser amount of ancillary laboratory material as well as through decreased personnel time. Somewhat similar to our cost-saving findings, Barreto et al have reported that the use of S/CO value as a determinant for further confirmation testing would be practical as well as more economical in anti-HCV testing (Barreto et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, through the use of a lesser number of test kits, blood banks could gain further cost reductions by using a lesser amount of ancillary laboratory material as well as through decreased personnel time. Somewhat similar to our cost-saving findings, Barreto et al have reported that the use of S/CO value as a determinant for further confirmation testing would be practical as well as more economical in anti-HCV testing (Barreto et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The data presented in this study demonstrated that high s/co ratios on the PRISM HCV ChLIA were predictive of confirmed‐positive results in our donor population, a finding that has previously been observed with other anti‐HCV screening IAs 1‐14 . A similar correlation between high s/co ratios and confirmed‐positive results was also found for the PRISM HBsAg, HIV O Plus, and HTLV‐I/II ChLIAs.…”
Section: Discussionsupporting
confidence: 87%
“…The data presented in this study demonstrated that high s/co ratios on the PRISM HCV ChLIA were predictive of confirmed-positive results in our donor population, a finding that has previously been observed with other anti-HCV screening IAs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] A similar correlation between high s/co ratios and confirmed-positive results was also found for the PRISM HBsAg, HIV O Plus, and HTLV-I/II ChLIAs. However, for all four PRISM assays there was a varying degree of overlap between the s/co ratio distributions for BFR and confirmed-positive results so that high s/co ratios were sometimes attributable to BFR results and, conversely, confirmed-positive samples sometimes gave low s/co ratios.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Systematic reviews were commissioned for the development of the WHO guidance on viral hepatitis testing services, described in detail in Amini et al [ 6 ] and Tang et al [ 2 ]. Those reviews identified only one study that had compared the diagnostic accuracy of different testing strategies and this was only for detection of anti-HCV [ 7 ]. As the published literature was unable to provide direct evidence to answer the question of a one-assay versus a two-assay testing strategy for HBsAg and for anti-HCV respectively, a model was developed using the principles of Bayesian statistics.…”
Section: Methodsmentioning
confidence: 99%